The determinants of intellectual capital disclosure among Malaysian listed companies - Taliyang, Siti Mariana; Abdul Latif, Rohaida; Mustafa, Nurul Huda (Institute for Business and Finance Research, 2001)
The objectives of this study are to identify the determinants and the extent of intellectual capital disclosure among Malaysian listed firms. The variables tested in this study are (1) age (2) size (3) leverage (4) profit; (5) ownership and (6) growth. A sample of 150 companies listed in Bursa Malaysia was selected consisting of five industries: Information Technology, Consumer Product, Industrial Product, Trading/Services and Finance. The result show that about 72.6 percent of the companies selected disclosed intellectual capital in their annual reports. That data show that our variables are determinants of intellectual age, size, director ownership and growth.